Membangun Kesadaran Etis Teologis sebagai Upaya Mitigasi Prostitusi Online bagi Generasi Muda Kristen - Wilayanto; Patangun, Efrain (SEKOLAH TINGGI TEOLOGI KIBAID MAKALE, 2024)
The phenomenon of online prostitution has become a scourge for the younger generation, triggering significant concerns. The ease of internet access, the anonymity it offers, and the potential for financial gain are the main attractions for individuals to fall into this practice. Therefore, this article examines the crucial role of building theological ethical awareness as a strategy to mitigate online prostitution for the younger generation. The church and government have a responsibility in this matter. The church should deepen Christian education for the church generation from an early age and care for those who practice prostitution. The government should enforce the law and open up employment opportunities so that the nation's generation can work and not resort to immoral practices to earn their living needs.. Fenomena prostitusi online telah menjadi momok bagi generasi muda, memicu kekhawatiran signifikan. Kemudahan akses internet, anonimitas yang ditawarkannya, dan potensi keuntungan finansial menjadi daya tarik utama bagi individu untuk terjerumus dalam praktik ini. Oleh karenanya, artikel ini mengkaji peran krusial pembangunan kesadaran etis teologis sebagai strategi mitigasi prostitusi online bagi generasi muda. Gereja dan pemerintah memiliki tanggungjawab dalam hal ini. Gereja hendaknya memperdalam pendidikan Kristen bagi generasi gereja sejak dini dan peduli kepada mereka yang hidup melakukan praktek prostitusi. Pemerintah hendaknya menegakkan hukum dan membuka lapangan kerja agar generasi bangsa bisa bekerja dan tidak lari pada praktek-praktek amoral untuk mencari kebutuhan hidup mereka